Determination of The Critical Period of Sweet Corn Plants (Zea Mays Saccharata Sturt) Against Weed - Safrina, Safrina; Baidhawi, Baidhawi; Hafifah, Hafifah (International Journal of Engineering, Science and Information Technology, 2024)
The critical period is a time when cultivated plants are very sensitive to the presence of weeds so that the disturbance caused by them can reduce the final yield. So, no the entire growing period of plants is affected by weeds. This critical period relates to the time of proper control so that the presence of weeds does not always require control measures. This research aims to determine the critical period for sweet corn (Zea Mays Saccharata Surt) against weeds and the effect of weeds on the growth and yield of sweet corn plants. This research was carried out at Gampong Mesjid, Kaway XVI, West Aceh Regency, Soil Science Laboratory and Pest and Disease Laboratory, Agroecotechnology Study Program, Faculty of Agriculture, Malikussaleh University, North Aceh from February to April 2024. This research used an experimental method of randomized block design (RAK), the single factor that consists of 10 treatments with 3 repetitions. P1: 0-15 DAP with weeds, P2: 0-30 DAP with weeds, P3: 0-45 DAP with weeds, P4: 0-60 DAP with weeds, P5: 0-Weedy harvest, P6: 0-15 DAP weeds free, P7: 0-30 DAP weeds free, P8: 0-45 DAP weeds free, P9: 0-60 DAP weeds free, P10: 0-DAP harvest free from weeds. The observation data were analyzed using analysis of variance, the treatment average was obtained through Duncan’s Multiple Range Test (DRMT) a the 0.05 level. The research results show that the critical period for sweet corn (Zea mays saccharata Sturt) for weeds is determined at the age of 16-30 days after planting. Weed control carried out between  16-30 days of plant age will not inhibit the growth and yield of sweet corn plants.